Understanding the electrochemical lithiation/delithiation process in the anode material for lithium ion batteries NiFeOPO4/C using ex-situ X-ray absorption near edge spectroscopy and in-situ synchrotron X-ray. (1st September 2018) - Aziam, H.; Garhi, G.; Tamraoui, Y.; Ma, L.; Wu, T.; Xu, G.L.; Manoun, B.; Alami, J.; Amine, K.; Saadoune, I.
Abstract: Nickel iron (III) oxyphosphate NiFeOPO4 (NFP) was successfully synthesized using solid-state route and modified with carbon layer using sucrose as carbon source. The electrochemical performances of the composite anode material NiFeOPO4 /C (NFP/C) vs. Li + /Li 0 were investigated at C/5 current rate and in a wide voltage window 0.01–3.0 V. During the first lithiation at C/5, NFP/C was able to uptake more than six lithium ions into the structure delivering a capacity of 736.63 mAh g −1 . In this study, NFP phosphate was characterized using XRD, SEM, EDS mapping, and Raman spectroscopy. The first cycle was investigated using high energy spectroscopies including: in-situ synchrotron X-Ray Diffraction and ex-situ X-ray Absorption Near Edge Spectroscopy (XANES). In-situ synchrotron XRD revealed that the crystal structure of NFP/C undergoes structural transformations leading to lower degrees of crystallinity during the first lithiation. Ex-situ XANES measurements disclosed that the redox reaction of iron and nickel during the first lithiation and delithiation is reversible.